Hubungan Sanitasi Dasar Rumah Tangga Dengan Kejadian Diare Pada Balita Di Kel. Galung Kec.Tapalang - Afrisandi, Wira; Ashari, Agus Erwin; Ahmad, Haeranah (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Mamuju, 2025)
number one killer of children in Indonesia. Diarrhea can attack all ages, but severe diarrheal disease with a high mortality rate occurs in toddlers. Basic sanitation conditions are closely related to the incidence of diarrheal diseases where the risk of diarrhea can be higher with poor basic sanitation conditions. There will be 2,273 cases of diarrhea among toddlers in Mamuju district in 2023. Galung Subdistrict is the area with the highest cases of diarrhea in the Tapalang Community Health Center working area.This study aims to determine the relationship between basic household sanitation and the incidence of diarrhea in toddlers in Kel. Galung, Kec. Tapalang. This research was conducted in June-July 2024 in Kel. Galung District. Tapalang. The research method used in this research is the descriptive method. Determination of the sample in this study used the total sampling method. The sample collection method uses an observation sheet containing the results of observations regarding the condition of clean water, latrines, waste and waste processing areas as well as a questionnaire that asks about the status of diarrheal disease in toddlers.Based on the data analysis carried out, it is known that there is a significant relationship between the provision of clean water and the use of toilets and the incidence of diarrhea in toddlers in Kel. Galung District. Tapalang. Meanwhile, there is no significant relationship between waste processing and waste water processing and the incidence of diarrhea in toddlers.The conclusion of this research is that there is a significant relationship between basic household sanitation and the incidence of diarrhea in toddlers in Kel. Galung District. Tapalang. The suggestions from this research are for the community to continue to pay attention to basic sanitation, especially the provision of clean water, use of latrines, waste management and management of household liquid waste in Kel. Galung District. Tapalang.